Association Between a Geriatric Trauma Resuscitation Protocol Using Venous Lactate Measurements and Early Trauma Surgeon Involvement and Mortality Risk. Issue 8 (26th July 2013) - Bar‐Or, David; Salottolo, Kristin M.; Orlando, Alessandro; Mains, Charles W.; Bourg, Pamela; Offner, Patrick J.
<x xml:space="preserve">Abstract</x> Objectives To investigate whether implementing a geriatric resuscitation protocol that uses lactate‐guided therapy with early trauma surgeon involvement is associated with lower mortality through the early recognition of occult hypoperfusion (OH). Design Prospective cohort study. Setting Level I trauma center. Participants All hemodynamically stable individuals with blunt trauma aged 65 and older admitted to the Level I trauma center from October 1, 2008, through December 31, 2011 (n = 1, 998). Measurements Mortality over time (according to quarter) was analyzed using an adjusted logarithmic regression model stratified according to the presence of OH. OH was defined as lactate of 2.5 mM or greater. Results Overall mortality was 3.9% (n = 78). Admission venous lactate was collected in 73.5% of participants, of whom 20.5% had OH (n = 301). In participants with OH, a significant decrease in mortality was observed over time (adjusted coefficient of determination (R2) = 0.66, P = .002). A smaller yet significant decrease in mortality rates in participants with normal perfusion status was also observed (adjusted R2 = 0.55, P = .01). Conclusion Early identification and treatment of OH in elderly adults with trauma using venous lactate‐guided therapy coupled with early trauma surgeon involvement was associated with significantly lower mortality. A protocol that uses lactate‐guided therapy with early trauma surgeon involvement should be followed to improve the care of elderly adults with trauma.